Advanced flux-weakening control strategy in electric motor drive for automotive applications - Zheng, Chengwei (Nanyang Technological University, 2024)
This dissertation investigates an advanced flux weakening strategy for permanent magnet synchronous motor (PMSM) control, especially for automotive applications. The development of electric vehicles has led to an increasing demand for high performance motors, and PMSM has become the first choice for motor drive control systems due to their high power density and high efficiency. However, the voltage and current constraints of the PMSM limit its speed range. Implementing flux weakening control is an effective way to extend the operating speed range of the PMSM so that the motor can continue to operate beyond its rated speed. The study includes the learning of PMSM control methods, planning of current operating points during motor operation, and a comprehensive analysis of multiple existing flux weakening control methods, identification of their limitations, and comparison of speed regulation capability and efficiency. Several representative flux weakening control methods will be selected to demonstrate their effectiveness and applicability through simulation experiments to meet the requirements of electric vehicle applications.